CALORIFIC VALUES AS FUNCTIONS OF MAIN BODY CONSTITUENTS IN SOME FRESHWATER TELBOSTS - Pal, B B; Pal, G P (Indian Journal of Fisheries, 2011)
Energy values of groups of small, medium and large size fishes of tome commeircially importEnt freshwater fishes have been determined using wet-oxidation method. The calorific values per unit of dry weight was significantly different (P <; 0.001) among three size groupis Of each species tested. The speoies-specificity of caloric content was in^’ariably observed (P <[ O.OOl) in all the fishes of small, medium and large size. iLow and Wgh calorific values were obtained in small and large size fishes respectively. As the organic carbon, organic matter and total nitrogen of the fish body increased with age, the energy content of the fishes also increased and was described by equstions of least squasre method.